Cultura organizacional: uma análise da microempresa familiar informal - Teixeira, Thiciane Mary Carvalho; Valentim, Marta Lígia Pomim [UNESP] (My University, 2011)
Analyze possible relationships between the bankruptcy and the family structure of informal micro-enterprises in Fortaleza city, Brazil. The analysis began with a research among micro-entrepreneurs who were beneficiaries of PROFITEC loans in bankruptcy and non-bankruptcy situation in 1997-1999 period. Evaluate whether the overlap of family and professional relationship inside the organizational structure of those micro-enterprises is a factor leading to bankruptcy. The comparative analysis divides the micro-enterprises into two groups: one that which had complied with the loan obligations (abiding firms) and another which had not (non-abiding firms). The analysis pointed out the familiar structure as having positive and negative influences over organizational work in both groups. The research also realized that those groups of family informal micro-enterprises do not recognize the professional problems related to the family, giving room for managerial conflicts related to the compliance, work time and use of profit. We cannot say that family structure of the informal microenterprises is the decisive cause for non-abidance, since there are also family firms which have the same disadvantages of both groups, but are complying with their obligations. The personal relationships in the informal family firms, however, define good practices and behaviors that definitely affect their operations.

Analisa as possíveis relações entre a inadimplência e a estrutura organizacional familiar das microempresas informais de Fortaleza. A análise partiu da pesquisa entre os microempresários beneficiados com o financiamento da PROFITEC em situação de inadimplência e adimplência, durante os anos de 1997 a 1999. Avalia se a superposição da relação familiar e profissional dentro da microempresa informal familiar se constitui em um dos fatores que contribui para a inadimplência. A análise comparativa entre as microempresas adimplentes e as inadimplentes constatou que há elementos positivos e negativos no trabalho em família em ambos os grupos. Constatou-se, também, que as microempresas informais familiares pesquisadas não reconhecem os problemas profissionais junto aos membros da família, produzindo os primeiros conflitos gerenciais relacionados à obediência, tempo de trabalho, utilização do lucro da microempresa. Não foi possível afirmar que a estrutura familiar da microempresa informal se constituiu na causa determinante para a situação de inadimplência, uma vez que há também microempresas informais familiares que convivem com as mesmas desvantagens do trabalho em família e estão em situação de adimplência. No entanto, as relações pessoais na microempresa informal familiar demarcam práxis e comportamentos que influenciam em seu funcionamento.
Organizational culture: an analysis of micro firms
Keywords: Cultura Organizacional; Gestão da Informação; Microempresa Familiar; Microempresa Informal; Mercado Econômico